Les dictionnaires des idées reçues ou les paradoxes de la mise en forme de l’esprit critique sur la société du XIXe siècle et ses discours - Rachwalska von Rejchwald, Joanna (Romanica Silesiana, 2021)
The article problematizes the form of the “para-dictionary” used by the authors of stereotypical collections in the 19th century (Flaubert, Rigaud, Bloy). The meaning of these numerous published collections, the outbreak of the nineteenth neo-encyclopedicism, is not limited to narrowly understood didacticism and bourgeois criticism of “bȇtise”. The form used in them is based on the paradox that determines its uniqueness. The starting point for studying this paradoxical form is the semantic tension between ossification, repetition, symbolized by the stereotype and literary character of these “para-dictionaries”, which through irony, humor, linguistic gloss, original selection are examples of creative transformation “ossified”, which is the opposite of originality and repeated. In the twentieth and twenty-first century, the use of the “para-dictionary” form leads to the redefinition of certain genres, as is the case with Genette’s innovative autobiography.